Multiple gender stereotype threats in motor performance and learning - Heidrich, C. V.; Cardozo, P.; Chiviacowsky, S. (Research Quarterly for Exercise and Sport, 2025)
Purpose: Stereotype threat occurs when individuals from stereotyped groups fear confirming a negative stereotype, which undermines performance and learning. This study compared the effects of multiple gender stereotype threats (ST) on motor performance and learning of a soccer dribbling task.